Computer simulation of photoinduced molecular motion and reactivity. (2002) - Garavelli, Marco; Bernardi, Fernando; Roob, Michael A.; Olivucci, Massimo
Abstract : The use of the computer to simulate light induced chemical processes has given access to a detailed description of the molecular motion and mechanism underlying the reactivity of organic and bio-organic chromophores. Thus, different computational strategies and tools can now be operated like "virtual spectrometers" to characterize the photoinduced molecular deformation and reactivity of a given chromophore. Furthermore, a systematic computer investigation of a wide range of photochemical organic reactions during the last decade, has lead to novel concepts that allow the chemist to formulate the mechanism of a photochemical reaction in a rigorous way and with a language which is familiar to chemists. In this review we will revise some basic mechanistic concepts which have emerged in the novel field of computational photochemistry. These comprise the concept of conical intersection funnels, photochemical paths, path branching and selectivity. Recent work in the field of biological photoreceptors has demonstrated that computational chemistry can be successfully applied to photobiological problems. Here we will revise the results of the photoisomerization path mapping of the protonated Schiff base of retinal, the chromophore of rhodopsin proteins. These studies have produced the "two-state two-mode model" which provides a description of the photon-induced molecular motion in the isolated retinal chromophore. Such model represents a substantial revisionof the previous models for the primary event invisioninan imals and light driven proton-pumping in halobacteriae.